Wireless Communications through a Simplified Architecture Based on Time‐Domain Digital Coding Metasurface. Issue 7 (27th February 2019) - Dai, Jun Yan; Tang, Wan Kai; Zhao, Jie; Li, Xiang; Cheng, Qiang; Ke, Jun Chen; Chen, Ming Zheng; Jin, Shi; Cui, Tie Jun
Abstract: Tailoring the electromagnetic responses by metasurface greatly expands one's capabilities to manipulate light in a controlled manner. Either amplitude or phase of the incident wave can be altered during the light–matter interaction, and thus opens the possibility of information modulation without conventional analog or digital circuits. A prototype of quadrature phase‐shift keying (QPSK) wireless communication based on time‐domain digital coding metasurface, whose reflection properties can be varied within different time slots by changing the biasing voltages of varactor diodes in specially designed meta‐atoms, is developed here. As the information is transformed into binary bit streams and mapped to pulse sequences of the biasing voltage, the baseband digital signal is directly modulated to the carrier wave through the digital coding metasurface. Compared to the earlier version of binary frequency‐shift keying architecture based on digital coding metasurface, the proposed QPSK system has a much higher data‐transmission rate for wireless communications. A proof‐of‐concept experiment is conducted to prove the real‐time transmission ability of this system, where a video is delivered between the transmitter and receiver with high accuracy and date rate. The presented work is promising in the development of next‐generation wireless communication technologies. Abstract : A prototype of time‐domain digital coding metasurface based wireless communication system is proposed in this work. The baseband signal is directly modulated to the carrier wave by the metasurface. The system demo can realize real‐time video transmission with high data rate and high reliability. The presented work is promising in the development of next‐generation wireless communication technologies.